Ceramic tiles waste as coarse aggregates partial replacement for concrete production - Muhammad Fathi, Asrul (2015)
In accordance with conservation efforts, this research focuses on ceramic tile waste as partial coarse aggregates replacement for concrete production, prevention of environmental pollution with considering the elements of sustainable and cost-saving construction projects, especially material usage. Moreover, many of the construction industry in Malaysia produce construction waste that contributes largely in solid waste. Utilising ceramic tile waste, this research will focus on ceramic wastes obtain from the construction industry in Malaysia. Presently, much of ceramic industries production goes to waste, which is not undergoing the recycle process yet. A total forty cubes with the same dimensions (100 mm x 100 mm x 100 mm) were cast with five different proportion. Eight cube as one type of control proportion that is 0 % percentage of ceramic waste as partial replacement of coarse aggregates and the remaining 32 cubes are 5% ,10 % ,15% and 20% of ceramic as partial replacement of coarse aggregates. Besides that, all other parameters are constant. The concrete cube were tested as destructive test at last which is compression test that to find out compressive strength of specimens of hardened concrete at 3 days, 7 days and 28 days .Before undergoing the destructive test, the performance of the concrete was determined by undergoing slump test, compressive strength test, Ultrasonic Pulse Velocity test, Rebound Hammer test and water absorption test. From the results of the study, samples of concrete with 15% ceramic coarse aggregate replacement (A4) has reached optimum strength. Findings showed that concrete containing Ceramic Tile 15% showed the highest amount of strength compared with other specimen. Addition of 15% ceramic material has led to compaction of concrete structures in ceramics and exhibit low water absorption rate.